Social policy design: Psychological determinants of non-take-up in the era of digital and virtual governance - Cabral, M.; Jerónimo, R.; Calheiros, M. M. (XIII PhD Meeting in Social and Organizational Psychology, 2017)
Information and communication technologies (ICTs) are changing the way citizens relate to public administration / government. However, studies show that this virtual citizen-to-government relationship with the so-called e-Government, may also determine limits to everyone’s access to online platforms, not only due to their material conditions, but also to individual, psychological and social variables relevant to understanding of non-take-up via e-Government portals. The present study, based on 4 studies distributed in 3 tasks, aims to explore the variables that precede access in the digital age, related to the replacement of personal contact by online social policy platforms, associating the impact of these variables with the social stigma and to the theory of social dominance. The aim is to build an outcome for public policies that makes it possible to anticipate the psychological and social determinants of non-access and enhance citizens’ access to e-Government.